Improvement Of the Development of Tolerance Skills in Future Teachers (Example of Training a Military Course of Work) - A’zamov Inom Salimjonovich (Genius Journals, 2022)
National experience on philosophical, methodological, methodological, psychological and pedagogical approaches, as well as education of future teachers in the teaching of the military course of work in the spirit of military patriotism, as well as on the organization of educational activities of our republic and foreign scientists, as well as group and commanders; it is determined by the application of mutually complementary research methods, corresponding to the research tasks, the amount of analysis and the description of the study, as well as the qualitative provision, the reproducibility of the experimental and test work, as well as the processing of the results obtained using the methods of mathematical and statistical analysis. In this article, the development of tolerance skills in future pedagogues (on the example of training a military course of work) will be considered. In this side, the scientific and objective feedback of the teacher and the student on the methods and stages of improvement of the process of tolerance, development of pedagogical communication, education of tolerance in the process of tolerance are described.
Keywords: Nobility; military patriotism; pedagogical nobility; tolerance